2005
DOI: 10.1016/j.jmwh.2005.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Competencies Essential for Health Care Professionals in Primary Care

Abstract: The completion of the sequencing of the human genome in 2003 signaled the onset of the genomic era in health care. The knowledge gleaned from the Human Genome Project has led to the understanding that every health problem has a genetic component and that clinicians should include the application of genetic information in all aspects of health care. This article describes the genetic competencies essential for all health care professionals in primary care. Health care professionals should augment their current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…[59][60][61] As gatekeepers, PCPs need to know how to interpret genetic test results, understand when to refer and ask for second opinions of genetic professionals, 59,62,63 and address complex personal, cultural, ethical, legal, and social issues associated with genetic testing. 59 This review confirmed relatively low levels of objective and subjective genetic testing-related knowledge among PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] As gatekeepers, PCPs need to know how to interpret genetic test results, understand when to refer and ask for second opinions of genetic professionals, 59,62,63 and address complex personal, cultural, ethical, legal, and social issues associated with genetic testing. 59 This review confirmed relatively low levels of objective and subjective genetic testing-related knowledge among PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…13,31,37,38 However, research has shown that many HCPs practising in primary care do not have genetic competence, that is, they do not possess the necessary genetic knowledge or skills to fulfil such roles. [37][38][39][40][41][42][43][44][45][46] Researchers investigating HCPs' genetic competence, practice and/ or behaviour, have mainly collected data via surveys and questionnaires where HCPs self-report information. 27,37,[43][44][45][46][47][48][49][50][51] There are limitations in these types of studies regarding the validity of the data obtained in terms of how much they reflect the actual situation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, members of the National Coalition of Health Care Professional Education in Genetics-an interdisciplinary group representing more than 120 diverse health professional organizations, consumer and voluntary groups, government agencies, private industries, managed-care organizations, and genetics professional societies-developed and agreed on a list of core competences in genetics (Engstrom, Sefton, Matheson, & Healy, 2005;Van Riper & Gallo, 2005). These competencies represent the minimum knowledge, skills, and attitudes necessary for health care professionals from all disciplines to provide patient care that involves awareness of genetic issues and concerns.…”
Section: Development Of Core Competencies In Genetics and Genomicsmentioning
confidence: 99%